Aquaporin‐1 in breast cancer. Issue 1 (23rd November 2021) - Traberg‐Nyborg, Laura; Login, Frédéric H.; Edamana, Sarannya; Tramm, Trine; Borgquist, Signe; Nejsum, Lene N.
Abstract : The canonical function of aquaporin (AQP) water channels is to facilitate passive transport of water across cellular membranes making them essential in the regulation of body water homeostasis. Moreover, AQPs, including AQP1, have been found to be overexpressed in multiple cancer types, including breast cancer, where AQP1 overexpression is associated with poor prognosis. AQPs have been shown to affect cellular processes associated with cancer progression and spread including cell migration, angiogenesis, and proliferation. Moreover, AQPs can regulate levels of adhesion proteins at cell–cell junctions, a regulatory role, which is still largely unexplored in cancer. Understanding the molecular mechanisms of how AQP1 contributes to breast cancer progression and metastatic processes is essential to establish AQP1 as a biomarker and to develop targeted anticancer treatments for breast cancer patients. This mini‐review focuses on the role of AQP1 in breast cancer.